Certain Aspects of Accounts Receivable and Payable Analysis - Kharabadze, Elene; Jikia, Merab (Archives of Business Research, 2018)
One of the primary ways to improve sales and to develop business is to increase credit sales, in other words, to extend the terms of payment. This, in effect, increases the risk on nonpayment, which represents accounting loss that could materialize in bankruptcy. Therefore, it is necessary to develop effective system of accounts receivable management, which mainly depends on its current analysis and prognosis. Account receivable analysis should focus on the following aspects: evaluate the nature of receivable, predict the probable amount of receivable, implement sound credit policy, determine aging of receivable and develop matching mechanism between accounts receivable and accounts payable. On one hand, lenient credit policy creates more work for the firm because it has to analyze its customers, conduct aging and, subsequently, increase firms’ expenses. However, strict credit policy has its drawbacks as well. The primary disadvantage of strict credit policy is the loss of customers, which will also reduce revenue. The following conclusion was formed: the increase of turnover period of accounts receivable and inventory and the reduction of turnover period of accounts payable causes the reduction of cash and cash equivalents. Furthermore, the reduction of the turnover period of accounts payable and inventory and the increase of turnove